Paleonutrition - Sutton, Mark Q. (University of Arizona Press, 2010)
The study of paleonutrition provides valuable insights into shifts and changes in human history. This is the most comprehensive book on the topic. Intended for students and professionals, it describes the nature of paleonutrition studies, reviews the history of research, discusses methodological issues in the reconstruction of prehistoric diets, presents theoretical frameworks frequently used in research, and showcases examples in which analyses have been successfully conducted on prehistoric individuals, groups, and populations. It offers an integrative approach to understanding state-of-the-art anthropological dietary, health, and nutritional assessments. The most recent and innovative methods used to reconstruct prehistoric diets are discussed, along with the major ways in which paleonutrition data are recovered, analyzed, and interpreted. The book includes five contemporary case studies that illustrate the mutually beneficial linkages between ethnography and archaeology.